EFFECTS OF RESISTANCE TRAINING ON SPEED AND AGILITY IN SPRINTERS - Kabadagi, Basavanneppa B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Speed and agility are critical components of sprint performance, and resistance training has been widely utilized to enhance these attributes. This study investigates the effects of a structured resistance training program on speed and agility in sprinters. A total of 40 male and female sprinters (ages 18–25) participated in the study and were divided into an experimental group (n=20) and a control group (n=20). The experimental group followed a structured resistance training program in addition to their regular sprinting workouts, while the control group continued their standard sprint training without resistance exercises. Key performance indicators, including the 30-meter sprint time and agility T-test performance, were measured pre- and post-intervention over an eight-week training period. The results indicate that the experimental group showed significant improvements in sprinting speed (p < 0.05) and agility (p < 0.05) compared to the control group. These findings suggest that incorporating resistance training into sprint training regimens enhances neuromuscular efficiency, explosive power, and directional change ability, leading to improved sprint and agility performance. The study highlights the importance of resistance training for competitive sprinters and provides practical recommendations for integrating resistance exercises into sprint training programs.